Pengaruh Jarak Tanam dan Macam Varietas Terhadap Pertumbuhan dan Hasil Kubis Bunga (Brassica oleracea var. botrytis L.) di Lahan Sawah Tadah Hujan - Linda Marlina; Muharam Muharam; Yayu Sri Rahayu (Jurnal Ilmiah Wahana Pendidikan, 2021)
The experiment was carried out from April 2021 to August 2021 in Karangmulya village, Bojongmangu sub-distric, Bekasi district. The research method was carried out using experimental methods and the experimental design used a Randomized Block Design (RAK) with 9 treatments, namely A (40 cm x 50 cm + PM 126 F1), B (50 cm x 50 cm + PM 126 F1), C (50 cm x 60 cm + PM 126 F1), D (40 cm x 50 cm + Bima 45 F1), E (50 cm x 50 cm + Bima 45 F1), F (50 cm x 60 cm + Bima 45 F1), G (40 cm x 50 cm + Aquina F1), H (50 cm x 50 cm + Aquina F1), I (50 cm x 60 cm + Aquina F1). The result showed that combination of spacing and varieties increased the growth and yield of cauliflower (Brassica oleracea var. botrytis L.) in rainfed rice fields. The spacing of 50 cm x 50 cm and the Bima 45 F1 variety gave the best result on fresh wight per plant and flower fresh weight per plant, namely 446,4 grams and 325,33 grams, respectively.